Organizational, operational and interactional processes of people's participation in community activities in Malaysia. - Abu Samah, Asnarulkhadi; Aref, Fariborz (2010)
This study focuses particularly on how people living as one community organize themselves to fulfill their needs and expectations through various groups, as revealed and directed by respondents in the research process. Therefore, the analysis and interpretation of the data is based on the people's expressed experiences of participating in such processes by treating those experiences as one entity, regardless of the type of groups they represented.